Basilar invagination presenting as recurrent posterior circulation stroke with locked-in syndrome in a child: a case report - Kumar, Mukesh; Mehta, Pooja; Garg, Pawan K. (International Journal of Contemporary Pediatrics, 2017)
Basilar invagination is a type of craniovertebral junction anomaly which occurs when the tip of odontoid process migrates upward into the intracranial space through foramen magnum and most commonly present as progressive neurological deficit implicating the high cervical cord, lower brainstem and cranial nerves. It can rarely present as vertebro-basilar territory insufficiency and occlusion, leading to stroke. Treatment is typically surgical and continues to centre on varying combinations of anterior or posterior decompression with or without traction or fusion. We present a 13-year-old boy with basilar invagination diagnosed on MRI with angiogram, which was missed on initial presentation, leading to recurrent posterior circulation stroke progressed to Locked-in syndrome. This case report emphasis the need of screening for craniovertebral junction anomalies in young patients presenting with posterior circulation stroke.